Violence in a U.S. Veterans Affairs healthcare system: worker perspectives on prevalence, causes, and contributors. Issue 1 (2nd January 2017) - Purcell, Natalie; Shovein, Eric; Hebenstreit, Claire; Drexler, Michael
Abstract: Worldwide, violence in healthcare settings is a common occurrence, causing stress, injury, and burnout among healthcare workers, and impacting their ability to provide safe, effective care for patients. Using focus group data from a large, public veterans' healthcare system in the United States, this article examines how Veterans Affairs (V.A.) workers experience violence and aggression on the job, and how they describe the causes of and contributors to violence in their workplace. Across seven focus groups, 65 workers reported regular experiences of verbal aggression and less frequent exposure to physical violence. Perceived institutional contributors to violence included internal processes that are frustrating and difficult to navigate, workload concerns that increase stress, and safety deficits in the physical environment. Perceived cultural contributors included an absence of consequences for low-level patient aggression against healthcare workers and the need for a stronger ethos of teamwork. Many workers felt that the broader U.S. political context, including critical news media coverage and the public perception that the V.A. system is failing veterans, amplifies their vulnerability to abuse at work. Their experiences illustrate how broader sociopolitical and cultural dynamics can impact how safe workers feel and whether they feel supported in addressing and preventing workplace violence.